Teaching & Learning Guidelines [for SATLE Project] Online Module Development & Delivery - Wride, Michael (Trinity College Dublin, The University of Dublin, 2020)
This resource aims to introduce the Module designers to considerations for online module development & delivery.
Keywords: Instructional design, principles